Manipulation of Barley Development and Flowering Time by Exogenous Application of Plant Growth Regulators - Kupke, Brendan M.; Tucker, Matthew R.; Able, Jason A.; Porker, Kenton D. (Frontiers in Plant Science, 2022)
Matching flowering time to the optimal flowering period in Mediterranean cropping zones is pivotal to maximise yield. Aside from variety selection and sowing date, growers have limited options to alter development in season. Plant hormones and growth regulators are used in perennial horticultural systems to manipulate development and floral initiation. In this study, a range of plant hormonal products were tested to analyse their effects on barley (Hordeum vulgare L) development by exogenous spray applications. Plants were grown in controlled conditions under long and short photoperiods with different vernalisation treatments. The gibberellin (GA) products demonstrated the greatest potential for altering development. The GA inhibitor trinexapac-ethyl was able to delay the time to flowering in genetically divergent barley cultivars by up to 200 degree days under controlled conditions. A similar delay in flowering could be achieved via application at both early (GS13) and late (GS33) stages, with higher rates delaying flowering further. Notably, trinexapac-ethyl was able to extend the duration of pre-anthesis phases of development. By contrast, GA3 was unable to accelerate development under extreme short (8 hour) or long (16 hour) day lengths. There was also little evidence that GA3 could reproducibly accelerate development under intermediate 10-12 hour day lengths. In addition, sprays of the cytokinin 6-benzyladenine (6-BA) were unable to reduce the vernalisation requirement of the winter genotype Urambie. The present study provides baseline data for plant growth regulator treatments that delay cereal development. These treatments might be extended in field studies to align flowering of early sown crops to the optimal flowering period.